Gut microbiota in post-acute COVID-19 syndrome: not the end of the story - An, Yaping; He, Linlin; Xu, Xin; Piao, Meiyu; Wang, Bangmao; Liu, Tianyu; Cao, Hailong (Frontiers in Microbiology, 2024)
The coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), has led to major global health concern. However, the focus on immediate effects was assumed as the tip of iceberg due to the symptoms following acute infection, which was defined as post-acute COVID-19 syndrome (PACS). Gut microbiota alterations even after disease resolution and the gastrointestinal symptoms are the key features of PACS. Gut microbiota and derived metabolites disorders may play a crucial role in inflammatory and immune response after SARS-CoV-2 infection through the gut-lung axis. Diet is one of the modifiable factors closely related to gut microbiota and COVID-19. In this review, we described the reciprocal crosstalk between gut and lung, highlighting the participation of diet and gut microbiota in and after COVID-19 by destroying the gut barrier, perturbing the metabolism and regulating the immune system. Therefore, bolstering beneficial species by dietary supplements, probiotics or prebiotics and fecal microbiota transplantation (FMT) may be a novel avenue for COVID-19 and PACS prevention. This review provides a better understanding of the association between gut microbiota and the long-term consequences of COVID-19, which indicates modulating gut dysbiosis may be a potentiality for addressing this multifaceted condition.